Exploring situational leadership as a key competence in driving the implementation of the integrated development plan of a South African municipality - Nkosimbini, Aphiwe (Rhodes University, Faculty of Commerce, Rhodes Business School, 2020)
Situational leadership is relevant to any organisation responsible for the delivery of services. Senior public sector leaders must cultivate the characteristics necessary to drive the implementation of initiatives geared towards meeting the developmental objectives of local government. The introduction of the Integrated Development Plan (IDP) of the municipality for the political term beginning in August 2016 provided a prospect of investigating the management of the implementation of this strategic blueprint in the context of the type of leadership styles prevalent in the local government environment. This dissertation therefore elucidates the idea of situational leadership as a key competence in driving the implementation of the IDP. This is through an examination of the understandings of twelve managers involved in driving this implementation. This research took the form of an evaluation case study. The critical incident technique was used to establish from the managers, as part of the interviews, a particular incident relevant to the delivery of services in line with the IDP. The focus in engaging with research participants was on their exercise of leadership as managers through the various contexts/ situations that arise within their working environment. The perspective gleaned from the participants is one which demonstrates the application of the model of situational leadership in a given sector. Furthermore, the study pinpointed the need to consider situational leadership through situation-specific lenses that take on board the role of relationships, organisational culture and its perceived impact on the performance of the organisation. The Case Study of the application of situational leadership provides insight into the myriad of challenges faced by local government leaders in driving service delivery imperatives. This is achieved through interviews with participants and the use of inductive thematic analysis as a tool of analysis. It provides an example of the value to be derived from situational leadership for leaders wanting to reach new frontiers in the work that they do. Ultimately, the service delivery expectations must be satisfied by those on whom this responsibility falls.
Keywords: Municipal government -- South Africa -- Eastern Cape; Leadership -- South Africa -- Eastern Cape; Corporate culture -- South Africa -- Eastern Cape; Organizational behavior -- South Africa -- Eastern Cape; Situational leadership; Integrated development plan